Pengembangan Media Pembelajaran berbasis Augmented Reality pada Materi Sistem Tata Surya untuk Meningkatkan Pemahaman Konsep Murid Fase C Sekolah Dasar - Deka Saputra; Pina Ramadiana; Yunnani Yunnani; Lia Agesti; Rahmat Kurniawan; Ahmad Syarif; Destrinelli Destrinelli; Eko Kuntarto; Hendra Sofyan (Jurnal Pena Karakter : Jurnal Pendidikan Anak dan Karakter, 2026)
This study is motivated by the low conceptual understanding of students in abstract learning materials, particularly the solar system in IPAS (Integrated Science and Social Studies) at the elementary school level. This study aims to develop an Augmented Reality-based learning media that is valid, practical, and effective in improving students’ conceptual understanding. The research method used is Research and Development (R&D) with the ADDIE model, which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of this study were fifth-grade students of SDN 225/IX Kasang Solok. The instruments used included expert validation sheets, teacher and student response questionnaires, as well as pretest and posttest. The results showed that the validity level of the media obtained scores of 95.5 for media, 81.6 for language, and 96 for material, all categorized as very valid. The practicality level obtained a score of 97.3 from teachers and 81.5 from students, both categorized as very practical. Meanwhile, the effectiveness test results indicated an improvement in students’ learning outcomes, with an N-Gain score of 0.5540, which falls into the moderate category. Therefore, the Augmented Reality-based learning media developed is considered valid, practical, and effective for use in IPAS learning at the elementary school level.